Minangkabau Theme Park Di Padang Dengan Pendekatan Rumah Minangkabau - Witra Karima; Pedia Aldy; Mira Dharma S (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
West Sumatra is one of the provinces in Indonesia with a lot of natural potential that can be used as a natural and cultural tourism. Padang as the capital is the economic center also known as the city of art and culture. To improve and develop cultural tourism, needed a tourist spot that showing, conserve and kept Minangkabau culture. This cultural tourism will added value for tourists to knowing and understand about Minangkabau culture. MinangkabauTheme Park as a theme park to be a place of entertainment or recreation that presents attractions and other events for visitors. Approximatin methode of Minangkabau theme can make visitors knowing and understand about Minangkabau culture. The design of Theme Park will apply the Minangkabau House approach in order to create an old Minangkabau atmosphere and apply characteristics of Minangkabau house that can be showed. Based on function and theme of design produce the concept of